Hubungan Antara Panjang Langkah Dengan Keseimbangan Dinamis Pada Lanjut Usia - Pahlevi, Setia; , Sugiono S. Fis.,MH Kes (2016)
Background: The changing gait analysis in the elderly cause complaints such as the slowing pace of walking, so that the elderly are not able to walk as before. One is a stride length. The stride length is the distance between two consecutive placement on the same leg. Stride length starting from the right foot then left foot and right foot back, or vice versa. Factors that may cause a decrease stride length in the elderly is declining strength in the gastrocnemius muscle so it can not produce optimal flexion flantar can also be caused because of poor body control or because a sense of security that can be acquired when running with short steps. The balance is defined as the body's ability to maintain the body's center of mass to the plane of the pivot. The balance is a complex interaction of sensory and musculoskeletal systems are regulated in the brain in response to changing internal and external conditions. Objective: To know is there a relationship between the stride length with the dynamic balance in elderly. Methods: This type of research is observational with cross sectional approach. The sampling technique is purposive sampling with insklusi and exclusion criteria of 60 people. Test data analysis using test Spearmens Rank. Results: The results of data analysis showed no relationship between the length of step with the dynamic balance in the elderly with values (p <0.000) or p <0,05 so Ho rejected and Ha accepted. Conclusions: By using a cross sectional study concluded that there is significant correlation between the length of step with the dynamic balance in elderly. Keywords: Stride length, balance, elderly